Microaerophilic–aerobic sequential decolourization/biodegradation of textile azo dyes by a facultative Klebsiella sp. strain VN-31 - Franciscon, E. (2009)
Four different azo dyes were decolourized and biodegraded in a sequential microaerophilic–aerobic treatment by a facultative Klebsiella sp. strain VN-31, a bacterium isolated from activated sludge process of the textile industry. Dye decolourization was performed under microaerophilic conditions until no colour was observed (decolourization percentage >94%). The medium was then aerated to promote the biodegradation of the amines produced. The presence of aromatic amine in the microaerophilic stage and its absence in the aerobic stage demonstrate azo bond reduction and an oxidative biodegradation process, respectively. Total Organic Carbon (TOC) reduction for the growth medium plus dyes was ∼50% in the microaerophilic stage and ∼80% in the aerobic stage. The degradation products were also characterized by FT-IR and UV–vis techniques and their toxicity measured using Daphnia magna. The results provide evidence that the successive microaerophilic/aerobic stages, using a single Klebsiella sp. strain VN-31 in the same bioreactor, were able to form aromatic amines by the reductive break down of the azo bond and to oxidize them into non-toxic metabolites.